Arbeits(un)fähigkeit herstellen Arbeitsintegration von gesundheitlich eingeschränkten Erwerbslosen aus ethnografischer Perspektive - Koch, Martina (Seismo, 2018)
As most industrialised countries, Switzerland is increasingly attempting to (re)integrate people with health restrictions and disabilities into the job market. The reinforced political demand to reintegrate people with health restrictions challenges both the involved organisations and its employees. While the means and methods to assess (in)capacity for work are more and more refined, the according practices become more and more diverse. On the basis of an ethnography of two Swiss cantonal work integration agencies, this study analyses how the institutions under scrutiny construct and deal with their clients' (in)capacity for work. It reconstructs how "cases" of health restrictions are organisationally problematized, negotiated, and dealt with and examines the underlying logic of these practices and strategies.